Factors Influencing Complications of Percutaneous Nephrolithotomy: A Single-Center Study - Oner, Sedat; Okumus, Muhammed Masuk; Demirbas, Murat; Onen, Efe; Aydos, Mustafa Murat; Ustun, Mehmet Hakan; Kilic, Metin; Avci, Sinan (Urology Journal, 2015)
Purpose: Percutaneous nephrolithotomy (PNL) is a minimally invasive procedure used for successful treatment of renal calculi. However, it is associated with various complications. We assessed the complications and their potential influencing factors in patients who had undergone PNL. Materials and Methods: In total, 1750 patients who had undergone PNL from November 2003 to June 2011 were evaluated retrospectively. PNL complications and possible contributing risk factors (age, sex, serum creatinine level, previous operations, hydronephrosis, calculi size, localization, opacity, surgeon’s experience, accessed calyxes, number of accesses, and costal entries) were determined. Receiver operating characteristic (ROC) analysis was used to investigate the cutoff values of the data. Ideal cutoff value was determined by Youden’s J statistic. All the demographic and clinical variables were examined using backward stepwise logistical regression analysis. Continuous variables were categorized with logistic regression analysis according to the cutoff values. Results: Complications occurred in 396 (24.4%) patients who had undergone PNL. Hemorrhage requiring blood transfusion occurred in 221 (12.6%) patients, hemorrhage requiring arterial embolization occurred in 7 (0.4%) patients, perirenal hematoma occurred in 17 (0.97%) patients, hemo-pneumothorax occurred in 32 (1.8%) patients, and colon perforation occurred in 4 (0.22%) patients. Three patients (0.06%) died of severe urosepsis, and one patient (0.02%) died of severe bleeding. The calculus size, localization, access site, number of accesses, presence of staghorn stones, surgeon’s experience, and duration of the operation significantly affected the complication risk. Conclusion: Our retrospective evaluation of this large patient series reveals that, PNL is a very effective treatment modality for kidney stones. However, although rare, serious complications including death can occur.